Increased late urinary toxicity with whole pelvic radiotherapy after prostatectomy - Kragelj, Borut (Radiology and oncology (Ljubljana), 2009)
Background. Radiotherapy aimed at prostatic bed (PBRT) can prevent recurrence or reestablish remission in prostate cancer patients primarily treated with prostatectomy. In selected patients results may be improved with the additional irradiation of pelvic nodes (WPRT). Patients and methods. The objective of the study was to evaluate late toxicity of postoperative radiotherapy in 43 patients - 21/43 treated with WPRT. Dysuria, haematuria, nocturia, continence and obstructive urination problems as well as urgency, continence, frequency, pain and bleeding of defecations were prospectively registered and converted to a modified Radiation Therapy Oncology Group (RTOG)- late effects normal tissue (LENT) scoring system. Median tumour dose (TD) for PBRT was 64.8 (59.4-70.0) Gy and for WPRT 50.4 (48.0-56.0) Gy. Results. More important than the deterioration of intestinal function (worsening for 1 grade in 54% and >= 2 grades in 5% of patients) was the deterioration of urinary function (worsening for 1 grade in 33% and >= 2 grades in 26% of patients). This appeared to be more frequent in patients withWPRT than PBRT (67% vs. 50% of patients) especially in conjunction with WPRT TD > 52 Gy (deterioration in 71% of patients). Conclusions. Although several factors may influence increased urinary toxicity after WPRT, it seems reasonable to lower the urinary bladder dose as it possible with novel radiation techniques.
Keywords: Gastrointestinal System; Gastrointestinalni sistem; novotvorbe; okvare; prostata; Prostata, novotvorbe; prostate; Prostatectomy; Prostatektomija; Prostatic Neoplasms; Radiation Effects; radioterapija; Radiotherapy; Sečila; sečnik; tumor; Urinary Tract